The impact of drug error reduction software on preventing harmful adverse drug events in England: a retrospective database study. Issue 3 (12th July 2022) - Sutherland, Adam; Gerrard, William S; Patel, Arif; Randall, Michelle; Weston, Emma
Abstract : Introduction: The use of intravenous administration systems with dose error reduction software (DERS) is advocated to mitigate avoidable medication harm. No large-scale analysis of UK data has been attempted. This retrospective descriptive study aimed to estimate the prevalence of hard limit events and to estimate the potential severity of DERS events. Method: Twelve months of DERS data was obtained from two NHS trusts in England. Definitions for drug categories and clinical areas were standardised and an algorithm developed to extract hard maximum (HMX) events. Subject matter experts (SMEs) were asked to rate severity of all HMX events on a scale of 0 (no harm) to 10 (death). These were analysed by clinical area and drug category, per 1000 administrations. Results: A total of 745 170 infusions were administered over 644 052 patient bed days (PBDs). 45% of these (338 263) were administered with DERS enabled. HMX event incidence across the whole dataset was 17.9/1000 administrations (95% CI 17.5 to 18.4); 9.4/1000 PBDs (95% CI 9.2 to 9.7). 6067 HMX events were identified. 4604 were <2-fold deviations and excluded. HMX were identified in all drug categories. The highest incidence was antibacterial drugs (2.21%; 95% CI 2.13 to 2.29). Of the 1415 HMX events reviewed by SMEs, 747 (52.6%) were low/no harm. Drugs with greatest potential harm were antiarrhythmics (21.8/1000 administrations; 95% CI 16.3 to 29.1), parenteral anticoagulants (24.16/1000 administrations; 95% CI 15.3 to 37.9) and antiepileptics (20.86/1000 administrations; 95% CI 16.4 to 26.5). DERS has prevented severe harm or death in 110 patients in these hospitals. Medical and paediatric areas had higher prevalence of potentially harmful HMX events, but these were probably related to profile design. Conclusion: Compliance with DERS in this study was 45%. DERS events are common, but potential harm is rare. DERS events are not related to specific clinical areas. There are some issues with definition and design of drug profiles that may cause DERS events, thus future work should focus on implementation and data standardisation for future large-scale analysis.